Strategi Pemasaran dalam Pengembangan Bisnis Florist (Studi Kasus: Posie Florist Solo) - Rafiqha Aulia Datau; Eni Setyowati (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the marketing strategies of Posie Florist Solo in facing intense competition in the florist industry. Using a qualitative method and participatory approach, data were collected through observations and in-depth interviews with employees and the store owner. The results indicate that Posie Florist combines digital and traditional marketing strategies, including the use of social media (Instagram, Facebook, website, TikTok) and participation in bazaars and workshops. The implementation of a marketing mix that includes product innovation, competitive pricing, strategic location, and effective promotions helps them maintain their market position and enhance competitiveness.